2022
DOI: 10.1111/lam.13683
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic characterization of Lactiplantibacillus plantarum HOM3204 and its restoration effect on antibiotic-induced dysbiosis in mice

et al.

Abstract: Significance and Impact of the Study: Lactiplantibacillus plantarum HOM3204 was isolated from homemade pickled cabbage. Lact. plantarum HOM3204 showed excellent probiotic characterization in vitro tests. Lact. plantarum HOM3204 significantly restored the gut microbiota composition by increasing the abundance of Lactobacilli and Bifidobacteria and decreasing Enterococci, and improved antioxidative function by raising the concentrations of glutathione peroxidase (GSH-Px) and superoxide dismutase (SOD) in serum o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 57 publications
2
5
0
Order By: Relevance
“…Probiotics can inhibit intestinal pathogens by producing antibacterial compounds, compete for rejection by consuming limited nutritional resources or adhering to epithelial cells, or stimulate intrinsic microbial activity ( 2 ). This is consistent with the research results of Zhang ( 54 ) that Lactiplantibacillus plantarum HOM3204 can significantly increase the relative abundance of Lactobacillus in AAD mice and decrease the relative abundance of Enterococcus . At the same time, we also found that the efficacy of strain 2-33 on AAD mice was time- and dose-dependent, which was similar to the results of Ling’s ( 55 ) study on the efficacy of Clostridium butyricum and Bifidobacterium infanti on AAD mice.…”
Section: Discussionsupporting
confidence: 93%
“…Probiotics can inhibit intestinal pathogens by producing antibacterial compounds, compete for rejection by consuming limited nutritional resources or adhering to epithelial cells, or stimulate intrinsic microbial activity ( 2 ). This is consistent with the research results of Zhang ( 54 ) that Lactiplantibacillus plantarum HOM3204 can significantly increase the relative abundance of Lactobacillus in AAD mice and decrease the relative abundance of Enterococcus . At the same time, we also found that the efficacy of strain 2-33 on AAD mice was time- and dose-dependent, which was similar to the results of Ling’s ( 55 ) study on the efficacy of Clostridium butyricum and Bifidobacterium infanti on AAD mice.…”
Section: Discussionsupporting
confidence: 93%
“…In a previous study, we isolated a Lpb. plantarum strain, HOM3204, from homemade pickled cabbage [ 9 ]. In vitro, Lpb.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro, Lpb. plantarum HOM3204 showed strong tolerance to simulated gastric and intestinal juice, high adhesion to Caco-2 cells, and good antimicrobial activity [ 9 ]. It significantly recovered the intestinal flora in ampicillin-induced dysbiotic mice by decreasing the abundance of Enterococci , while increasing the abundance of Lactobacilli and Bifidobacterium .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of this study showed that the consumption of GABA enhanced the modulation of norepinephrine and triggered the overexpression of the endothelin-1 protein, which is one of the most relevant factors affecting the hypertension modulation. These wide benefits of GABA and probiotic microorganisms, like L. plantarum strains, have opened a new possibility to address the demand of new functional ingredients (Zhang et al, 2022a;Jin et al, 2022). Considering the abovementioned background, the objective of the present study was the characterisation of the probiotic ability and safety of L. plantarum K16 strain isolated from Kimchi.…”
Section: Introductionmentioning
confidence: 99%